Constructing Financial Trust in Platform-Based Finance: A Grounded Theory Study of SME Sustainability in Emerging Economies - Ruben M Nayve Jr (Universitas 17 Agustus 1945 Surabaya, 2026)
The rapid expansion of platform-based finance has created new opportunities for small and medium-sized enterprises (SMEs) to access financial services, particularly in emerging economies where traditional banking remains limited. However, existing research has largely focused on access and adoption, offering limited insight into how SMEs develop trust in digitally mediated financial systems and how such trust shapes long-term sustainability. This study addresses this gap by examining how financial trust is constructed in platform-based finance and how it contributes to SME resilience. Drawing on a grounded theory approach, the study analyses qualitative data from SMEs across multiple emerging economies engaging with a range of platform-based financial services, including peer-to-peer lending, e-wallets, and marketplace-based financing. The findings reveal that trust does not precede engagement but emerges through an iterative process of interaction, evaluation, and adjustment. SMEs initially approach platform-based finance with caution, engage in controlled experimentation, and gradually develop conditional trust based on accumulated experience. Over time, this trust may stabilise, enabling the integration of platform-based finance into core business practices. The study shows that the impact of digital finance on SME sustainability is not direct. Rather, it is mediated by the construction of financial trust, which allows SMEs to move from fragmented and reactive usage toward more strategic and consistent financial behaviour. This transition strengthens adaptive capacity, improves financial flexibility, and supports continuity under conditions of uncertainty. Theoretically, the study contributes by conceptualising trust as a dynamic and processual construct embedded within platform ecosystems, rather than a static determinant of adoption. It also extends the literature on SME sustainability by linking trust construction to long-term resilience. Practically, the findings highlight the importance of transparency, consistency, and user experience in building trust, as well as the role of policy and institutional support in enabling more stable digital financial ecosystems.